\frac{5}{x { }^{2} - xy } + \frac{4}{y {}^{2} - xy} = - \frac{1}{6} \\ \frac{7}{x {}^{2} - xy } - \frac{3}{y {}^{2} - xy } = \frac{6}{5}

ино7 ино7    3   02.09.2019 23:21    1

Ответы
дтш дтш  06.10.2020 13:25

(5; 3) и (-5; -3)

Пошаговое объяснение:

{x}^{2} - xy = k \\ {y}^{2} - xy = u \\ \\ = \\ \frac{5}{k} + \frac{4}{u} = - \frac{1}{6} \\ \frac{7}{k} - \frac{3}{u} = \frac{6}{5} \\ = \\(k.u) = (10. - 6) \\ = \\ {x}^{2} - xy = 10 \\ {y}^{2} - xy = - 6 \\ \\ xy = {x}^{2} - 10 \\ xy = {y}^{2} + 6 \\ = {x}^{2} - 10 = {y}^{2} + 6 \\ {x}^{2} = {y}^{2} + 16 \\ x = \sqrt{ {y}^{2} + 16 } \\ = \\ {y}^{2} - y \sqrt{ {y}^{2} + 16 } + 6 = 0 \\ = y = 3 = x = 5

Т.к. (-3)²=3², (-5)²=5² и -3×(-5)=3×5, то подходит и решение (-5; -3).

ПОКАЗАТЬ ОТВЕТЫ
Али20061111 Али20061111  06.10.2020 13:25

Решение в файле. Там же иииии ответ.)


[tex] \frac{5}{x { }^{2} - xy } + \frac{4}{y {}^{2} - xy} = - \frac{1}{6} \\ \frac{7}{x {}^{2} - xy
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика